2015
DOI: 10.1002/jmri.25082
|View full text |Cite
|
Sign up to set email alerts
|

Rapid lung MRI in children with pulmonary infections: Time to change our diagnostic algorithms

Abstract: Rapid lung MRI was found to be comparable to MDCT for detecting thoracic abnormalities in pediatric patients with clinically suspected pulmonary infections. It has a great potential as the first line cross-sectional imaging modality of choice in this patient population. However, further studies will be helpful for confirmation of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 35 publications
3
60
0
Order By: Relevance
“…Only three studies have compared MRI for the detection of lung consolidation against computed tomography as the gold standard (table 2). [64][65][66][67][68][69][70][71] Other studies have compared MRI findings with chest radiography; however, these studies provide weak evidence because chest radiography is considered an inadequate gold standard (table 2).…”
Section: Advances In Radiological Diagnosismentioning
confidence: 99%
“…Only three studies have compared MRI for the detection of lung consolidation against computed tomography as the gold standard (table 2). [64][65][66][67][68][69][70][71] Other studies have compared MRI findings with chest radiography; however, these studies provide weak evidence because chest radiography is considered an inadequate gold standard (table 2).…”
Section: Advances In Radiological Diagnosismentioning
confidence: 99%
“…Ultrasound and magnetic resonance imaging (MRI) are the imaging modalities that do not involve any ionizing radiation and, hence, are safe to use in children [5][6][7][8][9][10]. NASH is conventionally diagnosed with the help of classical USG liver findings along with elevated serum levels of alanine aminotransferase (ALT) [1].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, thoracic MRI was found accurate in detecting hilar and mediastinal LAPs, cardiac findings, moderate to severe chronic interstisitial parenchymal changes except mild ground glass opacity, bronchiectasis, subpleural‐intraparenchymal cysts, and nodules smaller than 3 mm in one case with stage 4 sarcoidosis. Due to low signal intensity those subtle parenchymal findings may not be demonstrated well which is considered as a failure of MRI in the literature . However, this condition should not rule out the clinical importance of MRI for routine follow‐up or monitoring of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Due to low signal intensity those subtle parenchymal findings may not be demonstrated well which is considered as a failure of MRI in the literature. 10,12,18 However, this condition should not rule out the clinical importance of MRI for routine follow-up or monitoring of disease progression. Based on our results, thoracic MRI might be more likely to be used in late stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation